Critical to the clinical value of anthropological anomalies of the skull in Forensic Psychiatry and Criminal Anthropology (From the lessons of Professor Pasquale Penta 1899-1900 academic year) - Licata, Marta; Fusco, Roberta; Iorio, Silvia; Tesi, Chiara (Medicina Historica, 2019)
Criminal Anthropology is a very interesting chapter in the History of Psychiatry of the second half of the nineteenth century and the beginning of the twentieth. Here, we present the point of view of Professor Pasquale Penta (1859-1904), director of the important Italian scientific Journal: Journal of Forensic Psychiatry, Criminal Anthropology and Affine Sciences, Psychiatric and Criminal Anthropologist, on the “anthropological anomalies”. He developed a position toward the clinical value of anthropological anomalies in forensic psychiatry diagnoses criticizing the excessive importance given also to individual anthropological anomalies.